Industry 4.0: Trends in Management of Intelligent Manufacturing Systems - Knapčíková, Lucia; Balog, Michal; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides a comprehensive exchange of information on current developments in the management of manufacturing systems and Industry 4.0. The book's contributions establish channels of communication and disseminate knowledge among professionals working in manufacturing and related institutions. It features submissions from experts, researchers, academicians and practitioners in relevant fields, who share their knowledge from the field of management of manufacturing systems. The book's main theme is Management of Manufacturing Systems with support for Industry 4.0, Logistics and Intelligent Manufacturing Systems and Applications, Cooperation management and its effective applications. Topics include Logistics, RFID Applications, Industrial and Smart Logistics, Intelligent Manufacturing Systems and Applications, New Materials and Smart Technologies for Industry 4.0, Enterprise Information Systems, Innovation and Knowledge Management, and Sequencing solutions for Lean Manufacturing.
Introduction -- Industry 4.0 -- Case Studies in Logistics -- Case Studies with RFID Applications -- Economic Impacts in Logistics -- ICT Support for Industry 4.0, Industrial and Smart Logistics -- Intelligent Manufacturing Systems and Applications -- Enterprise Information Systems -- Manufacturing Cell Concepts in Manufacturing Systems -- RFID in Manufacturing -- RFID Technologies in Material Handling System -- Supply Chain Approaches -- Tools and Methods for Management Systems -- SMART Technologies -- Transportations, City, Workplaces, Modern trends in Manufacturing Management -- Clusters in SME -- Complexity of Supply Chain Management -- Decision-making processes -- Innovation and Knowledge Management -- Lean Management and Manufacturing -- Modeling and Simulation of Manufacturing Companies -- New Trends in Entrepreneurship -- New Trends in Crisis Management -- Production Management Approaches -- Process Management, Production Planning and Scheduling -- Quality Control and Management TPM, Sequencing solutions for Lean Manufacturing -- New materials and technologies -- Conclusion.
Keywords: Manufactures; Industrial Management; Business information services; Facility management; Machines, Tools, Processes; Industrial Management; IT in Business; Facility Management